Learning Irony in School: Effects of Metapragmatic Training - Olkoniemi Henri; Häikiö Tuomo; Merinen Milla; Manninen Jasmiina; Laine Matti; Pexman Penny M. (Cambridge University Press (CUP), 2025)
Irony comprehension requires going beyond literal meaning of words and is challenging for children. In this pre-registered study, we investigated how teaching metapragmatic knowledge in classrooms impacts written irony comprehension in 10-year-old Finnish-speaking children (n = 41, 21 girls) compared to a control group (n = 34, 13 girls). At pre-test, children read ironic and literal sentences embedded in stories while their eye movements were recorded. Next, the training group was taught about irony, and the control group was taught about reading comprehension. At post-test, the reading task and eye-tracking were repeated. Irony comprehension improved after metapragmatic training on irony, suggesting that metapragmatic knowledge serves an important role in irony development. However, the eye movement data suggested that training did not change the strategy children used to resolve the ironic meaning. The results highlight the potential of metapragmatic training and have implications for theories of irony comprehension.